ANALISIS KELAYAKAN & KEUNGGULAN BISNIS KOPI FILTER DI WILAYAH KABUPATEN TANGERANG - Andreas Kiky (Jurnal Bina Manajemen, 2019)
In business, it is very important to consider feasibility before conduct the operational activity. Nowadays, there are many cafes in South Tangerang Region. This phenomenon need a special attention because without proper calculation and feasibility study, these business can not survive in long-run. In this research, there are three feasibility aspects that will be examined. First is product aspect that consists of coffee taste and perception. Second is operational aspect, which consists of ambience and field condition and café traffic. Last aspect is the financial matter that represent by NPV and IRR. In general, this business is quite easy to enter. Unfortunately, the problem is this business not only sells the beverage but also sell the space for work and another activity. The challenge is investing a sum of money in design and interior will prolonge payback period and increase the risk. Although it need large capital in the beginning, it is still feasible because there are very large markets in this region but need to carefully manage as the competition is also fierce. In order to achieve competitive advantages, this business need to create creative marketing campaign, promotion and innovative product as the nature of consumer retainer is very low.